Truth [videorecording (DVD)] - Vanderbilt, James; Blanchett, Cate, 1969-; Redford, Robert; Quaid, Dennis; Grace, Topher, 1978-; Moss, Elisabeth, 1982-; Greenwood, Bruce, 1956-; Mulroney, Dermot; Mapes, Mary (Sony Pictures Home Entertainment, 2016)
Newsroom drama detailing the 2004 CBS 60 Minutes report investigating then-President George W. Bush's military service, and the ensuing firestorm of criticism that cost anchor Dan Rather and producer Mary Mapes their careers.